Desire for fame: scale development and association with personal goals and aspirations - Gountas, J.; Gountas, Sandra; Reeves, R.; Moran, L. (Wiley InterScience, 2012)
The desire for fame appears to be an aspiration for many people, which is associated with material wealth, social recognition, and admiration. Recently, reality TV has provided the opportunity for ordinary people to become famous with little effort or outstanding achievement. A literature review revealed no scale to measure the desire for fame that is not specifically concerned with celebrity worship or personality, but related to the perception of lifestyle benefits associated with being famous. The key objective of this study was to develop a scale to measure the desire for fame and test its validity and reliability. The scale items were developed through the literature review and exploratory interviews. A pilot study was conducted to test the relationship between the desire for fame and external goals, which indicated positive associations. A second, online survey was conducted using a sample of 507 people. The Desire of Fame scale was found to have good psychometric properties and the findings suggest significant relationships with extrinsic and instrinsic aspriations, consistent with self-determination theory. The social and marketing implications of the research are discussed and suggestions have been made for future research.